2021
DOI: 10.1093/cvr/cvab294
|View full text |Cite
|
Sign up to set email alerts
|

Optical ventricular cardioversion by local optogenetic targeting and LED implantation in a cardiomyopathic rat model

Abstract: Aims Ventricular tachyarrhythmias (VTs) are common in the pathologically remodelled heart. These arrhythmias can be lethal, necessitating acute treatment like electrical cardioversion to restore normal rhythm. Recently, it has been proposed that cardioversion may also be realized via optically controlled generation of bioelectricity by the arrhythmic heart itself through optogenetics and therefore without the need of traumatizing high-voltage shocks. However, crucial mechanistic and translati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…While treating VT does not require multiple stimulation points, having the capacity to actuate from any required point on the heart is essential to stopping re-entry, because cardiac failure is a dynamic process with magnitude and locality of infarction changing from case to case clinically ( 21 ). In current technology, the computation of heart rate and the delivery of stimulation by these devices are achieved using multiple pieces of equipment or require researchers to interpret the data to determine and deliver the appropriate stimulus ( 22 , 23 ). The spatiotemporal accuracy of these devices is often limited by the size of the interface that delivers stimulus to the heart, which, in turn, is limited by the lack of flexibility of the biointerface.…”
Section: Introductionmentioning
confidence: 99%
“…While treating VT does not require multiple stimulation points, having the capacity to actuate from any required point on the heart is essential to stopping re-entry, because cardiac failure is a dynamic process with magnitude and locality of infarction changing from case to case clinically ( 21 ). In current technology, the computation of heart rate and the delivery of stimulation by these devices are achieved using multiple pieces of equipment or require researchers to interpret the data to determine and deliver the appropriate stimulus ( 22 , 23 ). The spatiotemporal accuracy of these devices is often limited by the size of the interface that delivers stimulus to the heart, which, in turn, is limited by the lack of flexibility of the biointerface.…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged illumination of ventricular areas leads to disturbance in the regular sinus rhythm with the generation of spontaneous ventricular extrabeats or complete block of electrical activity, used to terminate ventricular tachycardia in mouse heart (Bruegmann et al., 2010; Nyns et al., 2014). Earlier reports have shown that sustained illumination with ChR2(H134R) can enhance the vulnerability to spontaneous ventricular extrabeats but cannot suppress the activity due to lower sensitivity and poor penetration of blue light (Bruegmann et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…To date, various excitatory opsins, including ChR2, ChR2(H134R), CatCh and ReaChR, and inhibitory opsins, including NpHR and ArchT, have been used in cardiac optogenetics (Bingen et al., 2014; Bruegmann et al., 2010; Nussinovitch et al., 2014; Nyns et al., 2014; Park et al., 2014; Williams & Entcheva, 2015; Williams et al., 2013). ChR2(H134R), which generates large photocurrent, is one of the most used optogenetic actuators (Karathanos, Boyle et al., 2016; Williams & Entcheva, 2015; Williams et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…By allowing a spatio-temporal control of ion channel activity by light, both optogenetics and photopharmacology appear as promising approaches to equally solve the selectivity and temporal issues in treating arrhythmias. Impressive and convincing reports have illustrated the blooming power of optogenetics for the treatment of arrhythmias [8][9][10][11][12] .…”
mentioning
confidence: 99%
“…By allowing a spatio-temporal control of ion channel activity by light, both optogenetics and photopharmacology appear as promising approaches to equally solve the selectivity and temporal issues in treating arrhythmias. Impressive and convincing reports have illustrated the blooming power of optogenetics for the treatment of arrhythmias 812 . Nevertheless, while this approach is powerful, it suffers from one major drawback which is the need to genetically modify the heart in order to express photosensitive ion channels, which is irreconcilable so far with clinical applications.…”
mentioning
confidence: 99%